To chew or not to chew? Exploring the influence of scented chew toys on puppy chewing - Sonowal, Rituparna; Hall, Nathaniel J.; Stellato, Anastasia C. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionChewing and mouthing are natural oral behaviors in dogs, particularly during puppyhood, yet owners report these as nuisance behaviors. The provision of appropriate enrichment items, such as scented chew toys, are often recommended to reduce these undesirable behaviors. Nevertheless, the influence of providing scented chew toys on chewing and mouthing behavior in puppies has not been investigated.MethodsWe collected data on engagement levels in dogs (N = 29) with commercially available rubber chew toys during two 5-min sessions in an observation room, with each dog interacting with both toy types (non-scented, peanut butter-scented with squeaker) on separate days. Following the sessions, dogs were randomly assigned to be provided with either the non-scented (N = 15; control) and scented squeaker toy (N = 14) for 1 week in their household. Before and after the 1-week period, owners filled out an online questionnaire detailing how often their dog engaged in chewing and mouthing behaviors at home and they rated their agreement with various statements about their dog’s chewing behavior.ResultsDuring observation sessions, puppies spent more time interacting with (p = 0.02) and sniffing (p < 0.0001) the peanut butter-scented squeaker toy in comparison to the non-scented toy. The frequency of owner’s prompting the dog to engage with the toy during the observation sessions was higher for the non-scented toy than the peanut butter-scented squeaker toy (p < 0.0001). Descriptive statistics reveal that owners in the non-scented group were more likely to agree that their dog’s mouthing or nipping was problematic in the second survey (61.5%, + 16%) compared to the initial survey (45.5%), while owners in the scented group were less likely to agree (41.6%, –28.4%) compared to the initial survey (70%). Owner reports suggest no changes in the frequency of dogs chewing on undesired items and mouthing or nipping on body parts during the 1-week period for either toy type.DiscussionThe findings suggest that scent can enhance engagement with chew toys, and although chew toys did not influence owner perceptions, future research should evaluate the use of structured owner-implemented training strategies on mitigating unwanted chewing or mouthing behavior in dogs.